Pengaruh Kompetensi SDM dan Pemanfaatatan Teknologi Informasi Akuntansi terhadap Kualitas Laporan Keuangan Pemerintahan Kabupaten Sumba Timur - Abdian Tunu; I Komang Arthana; Herly M. Oematan (Dharma Ekonomi, 2025)
This study aims to obtain empirical evidence of the influence of human resource competence and the use of information technology on the quality of financial reports of the East Sumba Regency local government. The population in this study were all Civil Servants (PNS) in the East Sumba Regency OPD. Sampling was carried out by purposive sampling, namely the head of the financial sub-section, the expenditure treasurer and accounting staff. The research thesis human resource competence does not affect the quality of the East Sumba Regency local government financial reports. The use of information technology affects the quality of the East Sumba Regency local government financial reports, human resource competence and the use of information technology simultaneously affect the East Sumba Regency local government financial reports. In conclusion, the quality of the East Sumba Regency local government financial reports is influenced by the use of information technology, while human resource competence significant effect.